Do orthodontists consider endodontic complications in their orthodontic management of teeth with a history of dental trauma? A vignette survey - Kinda Awad; Ammar Al Hourani; Dariusz Kasperek; Fadi Jarad; Sondos Albadri (BMC Oral Health)
Abstract Background Dental trauma is a frequent injury seen commonly in young children. There is a link between malocclusion and the incidence of traumatic dental injuries. Orthodontic therapy has been suggested as a preventative measure in correcting unfavourable malocclusions and potentially avoiding traumatic dental injuries. To date, it is poorly understood if the complications reported following traumatic dental injuries are amplified during and following orthodontic treatment. The aim of this study was to evaluate whether orthodontists considered the endodontic implications associated with the orthodontic treatment of teeth with a history of dental trauma. Method A mixed methods vignette survey was designed, piloted, and distributed online to UK registered specialist orthodontists. The survey was split into three parts and consisted of three vignette clinical scenarios with open and closed questions. Results A total of 76 orthodontists responded from the United Kingdom. Of the participants, 46% (n = 35) of the orthodontists felt they had insufficient training in dental trauma and 42% (n = 32) lacked confidence in the treatment of traumatic injuries. The study participants reported non-standardised pre- treatment examination, limited dental trauma experience and insufficient training. In addition, 32% (n = 24) of clinicians felt that there is a lack of guidance in the orthodontic management of traumatised teeth and pulpal sequelae. Conclusion Orthodontists are not following a standardised protocol in their examination of teeth with a history of trauma prior to orthodontic treatment. There is a need within the orthodontic specialty to create a standardised protocol to assess teeth with a history of dental trauma.